Silicon‐based nanocomposites for thermoelectric application. Issue 3 (7th January 2016) - Schierning, Gabi; Stoetzel, Julia; Chavez, Ruben; Kessler, Victor; Hall, Joseph; Schmechel, Roland; Schneider, Tom; Petermann, Nils; Wiggers, Hartmut; Angst, Sebastian; Wolf, Dietrich E.; Stoib, Benedikt; et al.
Abstract : Here we present the realization of efficient and sustainable silicon‐based thermoelectric materials from nanoparticles. We employ a gas phase synthesis for the nanoparticles which is capable of producing doped silicon (Si) nanoparticles, doped alloy nanoparticles of silicon and germanium (Ge), Si x Ge1– x, and doped composites of Si nanoparticles with embedded metal silicide precipitation phases. Hence, the so‐called "nanoparticle in alloy" approach, theoretically proposed in the literature, forms a guideline for the material development. For bulk samples, a current‐activated pressure‐assisted densification process of the nanoparticles was optimized in order to obtain the desired microstructure. For thin films, a laser annealing process was developed. Thermoelectric transport properties were characterized on nanocrystalline bulk samples and laser‐sintered‐thin films. Devices were produced from nanocrystalline bulk silicon in the form of p–n junction thermoelectric generators, and their electrical output data were measured up to hot side temperatures of 750 °C. In order to get a deeper insight into thermoelectric properties and structure forming processes, a 3D‐Onsager network model was developed. This model was extended further to study the p–n junction thermoelectric generator and understand the fundamental working principle of this novel device architecture. Gas phase synthesis of composite nanoparticles; nanocrystalline bulk with optimized composite microstructure; laser‐annealed thin film. Abstract : The authors fabricated thermoelectric nanomaterials from doped silicon and silicon and germanium alloy nanoparticles, as well as composites of Si nanoparticles with embedded metal silicide nanoparticles. Processing was performed applying a current‐activated pressure‐assisted densification process for bulk samples and a laser annealing process for thin film samples. Devices were produced in the form of pn junction thermoelectric generators. A 3D‐Onsager network model was used to understand the fundamental working principle of this novel device architecture.